Conditions facilitating the participation of residents of older apartment complexes in community activities in Japan: basic study on community support measures - Yusuke Yabutani; Nobuhiro Yamada (Journal of Asian Architecture and Building Engineering, 2023)
The problem of social isolation is more acute in older apartment complexes, requiring the enhancement of community functions by encouraging residents to participate in community activities. This study aimed to identify the conditions that encourage residents to participate in community activities, based on each participation characteristic, in an older apartment complex. A questionnaire survey was conducted of all residents aged 20 years or older in the Akebono apartment complex in Sapporo City, Japan, and 201 responses were collected. Chi-square tests and residual analysis were used to clarify the attributes and participation conditions for each participation characteristic of the residents. Significantly more residents in their 70s living with their spouses were willing to participate on an ongoing basis. Participation conditions included a high level of community contribution, enjoyment, acquisition of skills, and interaction. Results indicated that residents who wanted to participate in the future were significantly more likely to be in their 50s and to have lived in the complex for less than five years; their requirements included hobby activities, enjoyment, and interaction. Residents who did not want to participate were significantly more likely to be in their 40s.